Air Pollution in NCR - Kumari, Kamlesh (Journal of Advanced Research in Alternative Energy, Environment and Ecology; Vol 5 No 1&2 (2018): Journal of Advanced Research in Alternative Energy, Environment and Ecology, 2021)
Since the past two decades, air pollution has become a global public health issue and identified as a major environmental health hazard. Due to rapid development, society is facing serious challenges such as: climate change, global warming, ozone hole, acid rain and smog. Increasing energy demand and growing per capita energy consumption has led to such serious challenges. Their notoriety is evidence for the growing concern about the human impacts on climate. Recently, the onset of winter in every year Delhi and National capital Region (NCR) of India witnessed hazy and dusty condition or smog, which prolonged for many days (October to November). In present investigation, on the basis of air quality monitored by various Government organizations for the years 2009 – 2015, the occurrence of smog in Delhi is studied and fog is categorized as mixture of Classical and Photochemical Smog. In present investigation the overall scientific aspects driving the research are as: important processes controlling levels of smog and surface exchange, impacts of smog on human health and the environment and important processes controlling the interaction between climate and air pollution.